The cross‐sectional association between diabetes and orthostatic hypotension in community‐dwelling older people. Issue 8 (11th December 2019) - Gannon, J.; Claffey, P.; Laird, E.; Newman, L.; Kenny, R.A.; Briggs, R.
Abstract: Aims: Orthostatic hypotension is a recognized complication of diabetes, but studies examining prevalence in diabetes are limited. The aim of this study was to ascertain the prevalence of orthostatic hypotension and the pattern of orthostatic BP response in a cohort of people with diabetes aged ≥ 50 years, embedded within the Irish Longitudinal Study of Ageing. Methods: Orthostatic hypotension was defined as a drop in systolic blood pressure (SBP) ≥ 20 mmHg or drop in diastolic blood pressure (DBP) ≥ 10 mmHg at 30 s after standing. Diabetes was defined by self‐report but cross‐checked against HbA1c and medication records. Multilevel mixed effects linear regression models were used to compare orthostatic BP in people with and without diabetes. Results: Some 3222 people were included, 7% (213 of 3222) of whom had diabetes. Prevalence of orthostatic hypotension in the group with diabetes was 22% (46 of 213) vs. 13% in those without diabetes; χ 2 = 12.43; P < 0.001. Multilevel models demonstrated prolonged recovery of DBP in people with diabetes, with only 41% (87 of 213) returning to baseline by 60 s. Logistic regression models demonstrated that diabetes was associated with a significantly increased likelihood of orthostatic hypotension (odds ratio 1.84, 95% confidence interval 1.30–2.59; P  = 0.001) and this remained robust after controlling for covariates. Conclusion: Over one‐fifth of older people with diabetes had orthostatic hypotension. Recovery of DBP is related to dynamic changes in total peripheral resistance and impairment of this baroreflex‐mediated response may explain the higher prevalence in diabetes. Given the prognostic implications when co‐existing with diabetes, orthostatic hypotension may represent a potentially modifiable risk factor for adverse outcomes in late‐life diabetes. What's new?: Older people with diabetes are thought to have impaired blood pressure (BP) recovery after standing but their pattern of orthostatic BP is not yet known and the prevalence of orthostatic hypotension in late‐life diabetes has not been established. We found that older people with diabetes have a 70% increased likelihood of having orthostatic hypotension at 30 s after standing. Recovery of diastolic BP is particularly slow, suggesting impairment of dynamic adjustments to total peripheral resistance may underpin this. Impaired BP recovery may represent an important modifiable risk factor for poorer outcomes in diabetes in later life, particularly in brain health.